KAJIAN PERAN BAHAN PEMUTIH NATRIUM PIROPOSPHATE (Na2H2P2O7) TERHADAP PROSES PEMBUATAN TEPUNG UBI JALAR - Welasih, Tjatoer; Hapsari, Nur (REKAPANGAN, 2011)
The  study  aims  to  determine  the  effect  of  bleaching  on  sweet  potato  flour.  The specified condition  is  weight  300  g  sweet  potato,  with  white  colour and Piroposphate Sodium  (Na2H2P2O7) concentration:  0;    0.3;  0.6;   0.9;  1.2  g  And  soaking  time:  5;  10; 15; 20; 25 minutes. The results obtained  the best degrees of color at concentration of 1.2 g with 25-minute immersion time of 30 TCU, the lowest obtained at concentrations of  0  g  0  minutes  by  long  immersion  in  the  amount  of  5.0  TCU.  To  obtain  the  best conditions  of  water  content  at  a  concentration  of  1.2  grams  with  a  long  soaking  25 minutes  in  the  amount  of  11.78%,  the  lowest  obtained  at  concentrations  of  0  g  0 minutes by long immersion in the amount of 7.8%. For  the largest starch content was obtained  at  a  concentration  of  0.6  g  with  25-minute  long  immersion  in  the amount  of 28.54%, the lowest obtained at concentrations of 0 g to 25 minutes long immersion in the amount of 26.66%.Keywords: Sodium Piroposphate, flour, sweet potatoes, bulbs, bleach